Yunpi Qufeng Chushi Formula for Pre-Rheumatoid Arthritis: Study Protocol for a Multiple-Center, Double-Blind, Placebo-Controlled Randomized Controlled Trial - Tang, Yujun; Li, Haichang; Huang, Lin; Wang, Qiao; Han, Yongmei; Wu, Huaxiang; Su, Xiao; Hou, Xiujuan; Huang, Chuanbing; Lin, Changsong; Tao, Qingwen; Tang, Jinyang; et al. (Frontiers in Pharmacology, 2022)
Introduction Rheumatoid Arthritis (RA) is an autoimmune disease characterized by multiple joints swelling and pain. Many factors contribute to the established RA, including gene risk factors, infection, and the environment. It may take a long time when a patient experience through health, pre-clinical RA (immune response exists but presents no clinical symptoms), pre-RA (immune response unbalance and present mild inflammatory arthritis), and established RA. Studies have shown the benefit in early RA disease control. However, when, whether, and how to intervene pre-clinical RA and pre-RA is still considerable debate. It has always Treat disease before it arises has always been an important part of Traditional Chinese Medicine (TCM) and has been validated in clinical applications. Thus, we would conduct a multiple-center, double-blind, placebo-controlled randomized controlled trial to evaluate Yunpi Qufeng Chushi Formula (YQCF) in preventing pre-clinical RA progression. Method The work is conducted as a 13-center, double-blind, placebo-controlled randomized controlled trial. 390 ages between 18-70 patients will be recruited in the trial. They will be randomly assigned to the intervention group (YQCF) and placebo group at a 1:1 ratio. The visit time points are set at baseline, the 3rd month, the 6th month, and the 12th month. The RA diagnoses (primary outcome), disease activity scores [using Disease Activity Score-28 for Rheumatoid Arthritis with CRP (DAS28-CRP), Clinical Disease Activity Index (CDAI), Simplified Disease Activity Index (SDAI)], TCM syndrome scores, and safety assessments will be recorded at every visit. Joint color doppler ultrasound, Health Assessment Questionnaire-Disability Index (HAQ-DI), The Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) will be recorded at baseline and the last visit. These tasks will be evaluated between time points. Safety assessments will be analyzed over the 12-month trial period. Discussion This work will provide evidence of TCM in preventing Pre-clinical RA progress to RA. However, whether early intervention would benefit the controlling RA disease still needed a long-term follow-up. Ethics and dissemination Protocol version 2 (201910-1). This research was approved by the Zhejiang Chinese Medical University Committee (2019-045). Results will be published in a peer-reviewed academic journal Trial registration numbers Registered at http://www.chictr.org.cn/index.aspx. Trial registration number: ChiCTR1900024166.